SENGGEGER âPELETâ: BUDAYA TURUN-TEMURUN MASYARAKAT SASAK LOMBOK SERTA PERGESERANNYA - Nasrulloh, Lalu (Proceeding SENDI_U, 2015)
Senggeger or familiar language is "pelet" is something so sacred to the people of Lombok. Senggeger is one of thehighly conserved Lombok culture until now. Supernatural powers contained in the senggeger science makescommunities preserve it for generations. Granting hereditary considered more efficacious than is obtained fromothers. The reason that makes people Sasak made senggeger as conquerors weapon womans heart. It is undeniable:why not enough people Sasak Lombok married one or two? Besides the Sasak Lombok has become a tradition fromancient times (divorce), strong beliefs against senggeger also be the cause of the Sasak Lombok happy married(many wives). Most people Sasak Lombok overall even have knowledge of the loving-compassion. Not to say theSasak Lombok, if you do not have Senggeger. Because it is hereditary it can be ensured everyone Sasak have it. Butit can not be denied, cultural or indigenous communities Sasak Lombok already began shifting, and of course thatbecame the cause is the development of technology. With the shift as it will lead to positive and negative influences,so it will affect the development of Sasak people of Lombok.Keywords: Culture Sasak Lombok, senggeger, and shift.